Potrzeby edukacyjne nauczycieli kształcenia zawodowego w świetle badań własnych - Monika Mazur-Mitrowska; Elżbieta Małek (Edukacja Ustawiczna Dorosłych)
The article was devoted to the analysis of the educational needs of vocational education teachers based on research conducted among 111 respondents from vocational schools in the Masovian Voivodeship. The research project was planned and carried out by the vocational education team operating at the Masovian Local Government Center for Vocational Development. Teachers answered questions about their educational needs, preferred forms and expected topics of professional development. The conducted research made it possible to obtain knowledge about the training needs of this group of teachers and will contribute to the development of an offer that meets their preferences.